2016
DOI: 10.1080/09593330.2015.1116609
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cd (II) from synthetic wastewater by alginate–Ayous wood sawdust (Triplochiton scleroxylon) composite material

Abstract: The biosorption characteristics of Cd (II) ions from synthetic wastewater using raw Ayous wood sawdust (Triplochiton scleroxylon), r-AS, immobilized by sodium alginate were investigated with respect to pH, biomass quantity, contact time, initial concentration of heavy metal, temperature and stirring rate. The experimental data fitted well with the Langmuir isotherm, suggesting that monolayer adsorption of the cadmium ions onto alginate-Ayous sawdust composite (a-ASC). The obtained monolayer adsorption capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 71 publications
2
16
0
Order By: Relevance
“…Taking into consideration the correlation coefficient (R 2 ), which for the pseudo-second order is between 0.99 and 1 (Table 2), it can conclude that MG sorption on CCAC can be classified as pseudo-second order, fact confirmed by the literature scientific results [5,6,35]. In addition, based on the fact that pseudo-second-order equation is derived on the assumption of a two-step reaction, we concluded that MG adsorption takes place as a twostep reaction scheme.…”
Section: Adsorption Kineticssupporting
confidence: 59%
See 1 more Smart Citation
“…Taking into consideration the correlation coefficient (R 2 ), which for the pseudo-second order is between 0.99 and 1 (Table 2), it can conclude that MG sorption on CCAC can be classified as pseudo-second order, fact confirmed by the literature scientific results [5,6,35]. In addition, based on the fact that pseudo-second-order equation is derived on the assumption of a two-step reaction, we concluded that MG adsorption takes place as a twostep reaction scheme.…”
Section: Adsorption Kineticssupporting
confidence: 59%
“…Among the inorganic and organic pollutants present in wastewater, dyes represent a strong threat because these contaminants are highly toxic, carcinogenic, mutagenic and teratogenic for human beings, fish species and microorganisms [1][2][3]. From literature, a series of physical, chemical and biological measures for the removal of dyes from effluents have been developed, such as adsorption [4][5][6], membrane separation [7], chemical coagulation [8,9], electrochemical method [10], or oxidative processes [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the case of treated WGT biomass after adsorption, a remarkable shift in positions of -OH and C=O bands was observed, which indicates that MG is binded mostly at these groups. [56][57][58][59] The changes in FTIR spectra confirm the binding of MG with functional groups present on the adsorbent surface. Similar observation were also reported by Pirbazari et al 25 The proposed adsorption mechanism would involve the connection realized between a lone pair of the oxygen atom in -OH and C=O and the nitrogen atom =N + (CH 3 ) 2 in the MG molecule.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%
“…Heavy metals are present in the environment, generally in very small amounts as trace elements, and are essential for life. However, these quantities can be enhanced by accumulation under the effect of human activities, thus becoming dangerous for ecosystems due to their toxicity and non‐biodegradability over time 3,5,6 . According to the precautionary principle within the agreement to comply with limiting values as they can be found in the European drinking water directive, human life is to be preserved with respect to consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Several processes have been developed for the removal of lead from wastewater in recent years including chemical precipitation, flocculation, ion exchange, electrolysis, membrane processes and adsorption. The latter has the advantage of being simple, efficient and economical as well as presenting great flexibility in design and operation 3,6,12 . However, conventional adsorbents (e.g.…”
Section: Introductionmentioning
confidence: 99%